Development of Rapid Agglutination Test to Detect Chicken Marek Antibody - I WAYAN TEGUH WIBAWAN; LIA SITI HALIMAH; TITIEK DJANNATUN; KAMALUDDIN ZARKASIE (Microbiology Indonesia, 2009)
To our knowlege, there is no rapid agglutination test to detect antibodies to viruses which might be due to the small dimension of viral particles. Through complex formation of Staphylococcus aureus bearing protein A-rabbit IgG-anti IgY-IgY anti Marek virus, agglutination of antibodies to viruses can be achieved and visualized. To design the prototype of the test, the bacterial cells of Staphylococcus aureus were coupled to a complex compound consisting of IgG-IgY-Marek antigen. This protocol was able to detect clearly the presence of Marek antibody in chicken sera, showing the rapid, clear and distinct agglutination reaction on the glass objects. No agglutination reaction was observed in the reaction of specified pathogen free chicken sera with this prototype showing the specificity of the test. This finding demonstrates a novel rapid agglutination which can be used for the detection of antibodies to various agents.